Financial technology and relationship lending: Complements or substitutes? - Kutzbach, Mark J.; Pogach, Jonathan (Journal of Financial Intermediation, 2024)
We describe the dimensions along which bank technologies differ from fintech competitors and construct a novel measure of a bank’s technology based upon its overlap with fintech firms in terms of granular product installation data. A one standard deviation increase in our financial technology measure is associated with an 8.3 percentage point increase in Paycheck Protection Program (PPP) loans in 2020Q2. We show that smaller banks benefited more from marginal technology gains, that technology facilitated out-of-area lending, and that technology complemented small banks’ branch-based in-area lending. In a difference-in-differences analysis, we show an outsized increase in small business lending growth in 2020 for high tech small banks relative to their peers.